Coloring Practice Learning Media Application In Early Childhood Using Live Coloring Technique - Nadia Berliana; Yulia Darmi; Agung Kharisma Hidayah; Ardi Wijaya (Jurnal Komputer, Informasi dan Teknologi, 2025)
Rapid technological advancements have had several negative effects on young children, as the majority of children now prefer playing with gadgets to studying. Childhood, from 0 to 8 years old, is considered a time for educational services. Drawing and coloring are common activities for learning and are a part of children's lives. Therefore, it is necessary to develop a learning pattern for children that combines two things they enjoy: coloring and gadget technology so that children can play with gadgets and learn what they enjoy at the same time. In this study, a learning application for coloring 3D objects was created using the Live Coloring Technique with Android -based Augmented Reality technology. The reason is because Android is a very popular and widely used operating system, making it easier to install and use the application